The Influence of Alternative Fuels on the Development of Large-Scale Production - Bobrova, Anna V.; Stepanov, Evgeny A.; Sakulyeva, Tatyana; Zhumabekova, Gaukhar Zh.; Yesturliyeva, Aigul I. (Journal of Environmental Accounting and Management, 2026)
The relevance of this research is that the ecological consequences were caused by the mass use of transport at the present stage. The purpose of the research is to compare the priority of large-volume production of two groups of fuels based on price and non-price factors; to identify the main development problems for all types of alternative fuel. The main problems were identified in the development of all types of alternative fuel and shown the possibilities of large-volume production of hydrogen and electric engines under the condition of the state’s active financial and legislative influence.